Determining the magnetic attempt time τ0, its temperature dependence and the grain-size distribution from magnetic viscosity measurements - Berndt,T; Muxworthy,AR; Paterson,GA (Journal of Geophysical Research. Solid Earth, 2015)
A new method to determine the atomic attempt time τ0 of magnetic relaxation of fine particles, which is central to rock and soil magnetism and paleomagnetic recording theory, is presented, including the determination of its temperature dependence, and simultaneously the grain-size distribution of a sample. It is based on measuring a series of zero-field magnetic viscous decay curves for saturation isothermal remanent magnetization at various different temperatures, that are later joined together on a single grain-size scale from which the grain-size distribution and attempt time are determined. The attempt time was determined for three samples containing non-interacting, single-domain titanomagnetites of different grain-sizes for temperatures between 27 K and 374 K. No clear temperature-dependent trend was found, however, values varied significantly from one sample to the other: from 10¹¹ s to 10 s; in particular, the sample containing multiple magnetic phases had an effective attempt time significantly lower than the more homogeneous samples, thereby questioning the applicability of the simple Néel-Arhennius equation for magnetic relaxation for composite materials.